A Review: Management of Alternaria and its Mycotoxins in Crops - Brian Gagosh Nayyar; Shaista Akhund; Abida Akram (International Journal of Advances in Applied Sciences, 2014)
The Deuteromycetes fungal genus Alternaria comprises of different saprophytic as well as endophytic species which are very common and worldwide in their occurance. Importance host plants include several crops. Alternaria spp. generally attacks the aerial ptarts of its host and early blight diseases caused by these fungi inflict serious damage to these crops. There is a growing concern of Alternaria spp. due to their ability to produce mycotoxins with different toxicological properties, which are harmful for human and animal health. Accurate identification of Alternaria spp. and their metabolites is a crucial phase in the implementation of preventive measures and controls in the system from farm to fork. Considering the importance of Alternaria spp. occurance on crops and Alternaria toxins risk assesment, additional studies in this area are indispensable.